Designing an Efficient Freelance Management System in Indonesia’s Event Industry: A Case Study of Evoria Event Orchestrator - Viga Sakina Ramadhanty; Leo Aldianto (Politeknik Pariwisata NHI Bandung, 2026)
This research aims to design an effective freelance management system for Indonesia’s event industry using qualitative research method of case study with Evoria Event Orchestrator. Evoria has over 900 freelancers and only about 10 percent are activ, indicating inefficiencies when it comes to recruiting, deployment, evaluation and retention of talent. Using the Design Thinking approach, this study integrates Getz’s (2012) Event Lifecycle, Cuskelly’s (2006) Volunteer Management Lifecycle, and Sullivan’s (2014) Employee Lifecycle Model to balance efficiency and empathy. The analysis identified six root causes, short preparation time, reactive culture, manual coordination, skill gaps, person dependent communication, and lack of feedback learning. Three solutions were developed: the Evoria Crew Planner, Evoria Coordination Manual, and Evoria Learning Hub and Freelance Circle, two were tested as prototypes. Findings confirm that structured yet human centered systems improve coordination speed, workload visibility, and freelancer engagement, offering a scalable model for efficience freelance management.